2003
DOI: 10.1182/blood-2002-09-2846
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase 2 trial of thalidomide in relapsed/refractory multiple myeloma: adverse prognostic impact of advanced age

Abstract: Relapsed or refractory multiple myeloma has a poor outlook. Some patients respond to thalidomide; however, criteria for predicting response have not been conclusively identified. We initiated a prospective multicenter phase 2 trial in patients with relapsed/ refractory myeloma using thalidomide up to the maximum dose, 800 mg/d. Interferon-␣-2B (1.5-3.0 ؋ 10 6 U, subcutaneously, 3 times per week) was added at week 12 if disease was responsive or stable. Patients intolerant of interferon continued thalidomide al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 37 publications
4
71
2
Order By: Relevance
“…19 Response rates of about 30% reported by Singhal et al 8 were confirmed by others groups. 9,[20][21][22][23] Addition of dexamethasone to thalidomide in patients who failed to benefit from prior therapy, including both thalidomide and dexamethasone given as single agents, further increased responses, up to an overall response rate of 50-55%. 10,11 These data suggested a synergy between thalidomide and dexamethasone and prompted several groups to explore this combination also in patients with previously untreated MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Response rates of about 30% reported by Singhal et al 8 were confirmed by others groups. 9,[20][21][22][23] Addition of dexamethasone to thalidomide in patients who failed to benefit from prior therapy, including both thalidomide and dexamethasone given as single agents, further increased responses, up to an overall response rate of 50-55%. 10,11 These data suggested a synergy between thalidomide and dexamethasone and prompted several groups to explore this combination also in patients with previously untreated MM.…”
Section: Discussionmentioning
confidence: 99%
“…Number of days to ANC4500/ml 11 (9-16) PLTC420 000/ml 14 (10-22) PLTC450 000/ml 17 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) PLT transfusions (no.) 3 (0-16) RBC transfusions (no.)…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate analysis of the OS of relapsed or refractory MM patients demonstrated that advanced age (exceeding 65 years) raised the serum level of LDH and also the concentration of creatinine predicted inferior outcomes (Mileshkin et al, 2003). Since an antiangiogenic effect is postulated as one of the most important mechanisms of THAL action pretreatment, angiogenesis was evaluated as a predictor of response.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, novel agents such as thalidomide, lenalidomide or bortezomib are associated with a higher risk of grade III or IV toxicities such as neuropathy, myelosuppression and thrombosis. [22][23][24][25] Hence, providers and patients may prefer the transient toxicity associated with auto-SCT2 in place of the continuous toxicities of novel agents. There is no evidence that the efficacy of future novel agent salvage Second SCT for myeloma WI Gonsalves et al therapies may be compromised by the prior sequence of salvage transplantation therapy.…”
Section: Discussionmentioning
confidence: 99%